2018
DOI: 10.1007/s11252-018-0784-4
|View full text |Cite
|
Sign up to set email alerts
|

Depleted suburban house sparrow Passer domesticus population not limited by food availability

Abstract: Little is known about the environmental factors that limit the demography and abundance of wild vertebrates in highly modified urban environments. The House Sparrow Passer domesticus is a globally widespread species whose urban populations have recently undergone substantial declines particularly in Europe. The environmental drivers of these declines remain unknown. In a previous study we showed that invertebrate availability during the breeding season limited reproductive success but not population size in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…For example, it has recently been reported that great tits could exclude flycatchers from nest‐boxes, and could even kill them in order to take over a nest‐box (Samplonius and Both ). However, this inter‐specific competition is also quite unlikely to explain our results because previous studies have suggested that house sparrows are dominant over tits for nest‐box occupancy (Charter et al 2013, Goldshtein et al ). Instead, our results suggest that house sparrows do not have to compete for cavities in urban landscapes similar to Niort.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, it has recently been reported that great tits could exclude flycatchers from nest‐boxes, and could even kill them in order to take over a nest‐box (Samplonius and Both ). However, this inter‐specific competition is also quite unlikely to explain our results because previous studies have suggested that house sparrows are dominant over tits for nest‐box occupancy (Charter et al 2013, Goldshtein et al ). Instead, our results suggest that house sparrows do not have to compete for cavities in urban landscapes similar to Niort.…”
Section: Discussionmentioning
confidence: 78%
“…For example, in many cities, old buildings are progressively replaced by new buildings, which are very often built with modern materials. These new structures without any cracks or cavities may preclude cavity nesters from breeding in cities and may cause population declines, especially in cavity‐nesting birds (Moudra et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Peach et al . [15] found a positive relationship between adult sparrow abundance and Eurasian sparrowhawk activity but no relationship between temporal trends in sparrow abundance and hawk activity. Studies on the impact of predation by domestic cats ( Felis catus ) have reached no definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these environmental changes have profound effects at the ecosystem level, modifying resource availability and ultimately breeding behaviour and fitness of urban populations 29 . For examples, correlative and experimental studies on insectivorous songbird breeding have shown that limited and poor-quality resource availability limits provisioning behaviour and reduces reproductive success in urban habitats [29][30][31][32][33][34][35] . Therefore, it is likely that differences in resource distribution and abundance as a result of urbanization may lead to certain parental behaviours to be more prevalent in urban areas with fitness consequences 36,37 .…”
mentioning
confidence: 99%